Development of Assessment Instruments for Fiqh Learning Based on Religious Moderation at Madrasah Tsanawiyah in West Java - Muhammad Aditya Firdaus; Ulfah (South Sulawesi Education Development (SSED), 2024)
This research was prompted by a preliminary study at MTs Cijaura, MTs Sirnamiskin, MTs Nurul Iman, and MTs Pulosari, which revealed that teachers have not been able to fully develop fiqh learning evaluation instruments that accommodate cognitive, affective, and psychomotor aspects for students with diverse understandings in Fiqh learning. The aim of this research is to develop a fiqh learning assessment instrument based on religious moderation at Madrasah Tsanawiyah. The research method utilized the R and D research ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with data collection techniques involving observation, interviews, questionnaires, and documentation. Qualitative data validity testing assessed the truth and reliability of the collected data, while quantitative data analysis employed validity and reliability tests. The results of this study indicate that the Fiqh learning assessment instrument can be developed based on the value of religious moderation. The development resulted in the following: 1) Fiqh learning assessment instruments containing religious moderation values, namely tawasuth, tasamuh, tawazun, and I'tidal; 2) Fiqh learning assessment instruments accommodating affective and psychomotor cognitive aspects; 3) The instruments developed received assessments from three expert validators-assessment validators, religious moderation validators, and fiqh field validators-with an average assessment value of 86.24, categorized as highly suitable and ready for testing; 4) The validity test results for the questions showed the largest r score of 0.651 and the smallest of 0.357, while the largest R table is 0.334 and the smallest is 0.321. The data indicates that the tested questions have an r count value greater than the r table, affirming the validity of the questions developed in the field; 5) The reliability test results have a Cronbach's Alpha score of 0.713, exceeding 0.05, confirming their reliability.